2004
DOI: 10.17796/jcpd.28.4.j634167443m061n3
|View full text |Cite
|
Sign up to set email alerts
|

Pulpectomies in primary incisors using three delivery systems: an in vitrostudy

Abstract: This in vitro study assessed the quality of pulpectomies in primary incisors using three filling systems: syringe with plastic needle, syringe with metal needle, and lentulo spiral. Preoperative radiographs of sixty extracted primary incisors were taken, canals were prepared and obturated.Postoperative radiographs taken in two directions were evaluated by two independent evaluators blinded to the technique used. Filling quality was determined by analyzing radiopacity, presence of voids and amount of material i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 3 publications
4
38
0
1
Order By: Relevance
“…In this study, root filling was performed in specimens with identical root canal anatomy and by a single operator, which makes the technique more reproducible and results more consistent. In primary teeth, some authors found better results NaviTip™ system compared with lentulo or syringe method using Vitapex ® as obturating material and better results for pressure syringes compared with lentulo for delivering Endoflas . Important to note that both studies used low resolution, bidimensional, and subjective evaluation techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, root filling was performed in specimens with identical root canal anatomy and by a single operator, which makes the technique more reproducible and results more consistent. In primary teeth, some authors found better results NaviTip™ system compared with lentulo or syringe method using Vitapex ® as obturating material and better results for pressure syringes compared with lentulo for delivering Endoflas . Important to note that both studies used low resolution, bidimensional, and subjective evaluation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Many laboratorial studies have been designed to investigate the effectiveness of different obturation techniques and filling materials for primary teeth, but most of them used radiographs or conventional tomographic evaluations . Although both techniques have very low spatial resolution (ranging from 100 to 1000 μm), radiographs have also de limitation of being a bidimensional evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal obturating technique should ensure a good apical seal without any underfilling or overfilling . Traditionally, zinc oxide eugenol (ZOE) has been the material of choice for filling root canals of primary teeth due to ease of handling, operator feasibility and cost‐effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Guelmann et al 53 assessed the quality of root canal fill by using three filling systems: syringe with plastic needle (Vitapex), syringe with metal needle, and lentulo spiral. Filling quality was determined radiographically.…”
Section: Easily Removedmentioning
confidence: 99%